Crystallographic and optical properties of wide bandgap photovoltaic semiconductor system, Cu(Al, In)Se2. (1st May 2022) - Yoneda, Ryoma; Beppu, Kosuke; Maeda, Tsuyoshi; Wada, Takahiro
Abstract: We characterized the optical and electronic properties of chalcopyrite-type Cu(Al, In)Se2, which is a candidate for wide-bandgap solar cell materials. The bandgap energy was determined from diffuse reflectance spectra. The bandgap energy increased from 1.00 eV for CuInSe2 to 2.61 eV for CuAlSe2 with an increase in the Al content. The ionization energy corresponding to the energy levels of the valence band maximum (VBM) was determined using photoemission yield spectroscopy. The VBM level of the Cu(Al, In)Se2 system stayed relatively constant, but the conduction band minimum level increased with increasing Al content. To analyze the local structures of Cu and In atoms in Cu(Al, In)Se2, Cu and In K-edge X-ray absorption fine structure (XAFS) spectra were measured at SPring-8. We discuss the crystallographic characteristics of Cu(Al, In)Se2 based on the results of the XAFS analyses and a comparison of the phase diagrams of the Cu2 Se–Al2 Se3, Cu2 Se–In2 Se3, and Cu2 Se–Ga2 Se3 systems.